Different Mathematical Functions - Sotimboeva Zarifakhon (Zien Journals, 2022)
This article about the production function of Cobb-Douglas is the technological ratio of the volume of labor resources and capital for the production of a certain amount of output. This model belongs to the two-factor model and was statically tested by the two Scientists Cobb and Douglas
Keywords: certain proportions allow; certain amount; Scientists Cobb and Douglas; function